Advanced bioengineering strategies broaden the therapeutic landscape for corneal failure - Al Monla, Reem; Daien, Vincent; Michon, Frederic (Frontiers in Bioengineering and Biotechnology, 2024)
The cornea acts as the eye foremost protective layer and is essential for its focusing power. Corneal blindness may arise from physical trauma or conditions like dystrophies, keratitis, keratoconus, or ulceration. While conventional treatments involve medical therapies and donor allografts-sometimes supplemented with keratoprostheses-these options are not suitable for all corneal defects. Consequently, the development of bioartificial corneal tissue has emerged as a critical research area, aiming to address the global shortage of human cornea donors. Bioengineered corneas hold considerable promise as substitutes, with the potential to replace either specific layers or the entire thickness of damaged corneas. This review first delves into the structural anatomy of the human cornea, identifying key attributes necessary for successful corneal tissue bioengineering. It then examines various corneal pathologies, current treatments, and their limitations. Finally, the review outlines the primary approaches in corneal tissue engineering, exploring cell-free, cell-based, and scaffold-based options as three emerging strategies to address corneal failure.